Management of recurrent chronic suppurative otitis media with cholesteatoma - Christianty, Finna; Wahyudiono, Ahmad Dian (PERHATI-KL, 2023)
Background: Chronic suppurative otitis media (CSOM) is a chronic inflammation involving the middle ear space and it became a burden especially in developing countries. Mastoidectomy remains the main treatment in CSOM with cholesteatoma. Recurrent cholesteatoma and suppurating process indicated the need of revision mastoidectomy. Purpose: Until now, study about the mechanism of recurrent cholesteatoma and its management still need further research. Case report: This paper reports a case of chronic suppurative otitis media with recurrent cholesteatoma which underwent revision mastoidectomy. Clinical Question : What are the factors associated with the occurrence of recurrent cholesteatoma and how to managed it? Methods: Evidence base literature study about chronic suppurative otitis media with recurrent cholesteatoma and surgery treatment was performed through PubMed, ProQuest, and Google Scholar database. Results: Recurrent cholesteatoma that occurred after mastoidectomy can be caused by residue of the cholesteatoma itself or new forming of retraction pocket. Revision mastoidectomy is necessary to evacuated the cholesteatoma and provide good drainage to the mastoid. Conclusion: Routine follow up after mastoidectomy is an important thing to help prevent recurrence of CSOM especially with cholesteatoma.